Tinjauan Komponen Utama Produk Wisata Di Kampung Tenun Solok Nan Indah (International Forum of Researchers and Lecturers, 2024)
This research is about insight into the main components of tourism products in the Solok Nan Indah Weaving Village, which is based on several problems related to tourist attractions, facilities in tourist destination areas, accessibility, destination image and prices for tourism. The research purpose is to analyze the main components of the tourism product in Solok Nan Indah Weaving Village. The research type used was quantitative with a survey method with a population of 329 respondents sample of 181 respondents with data collection techniques using a questionnaire with a scale of Likert which had been tested for validity and reliability. This research was processed using SPSS version 25.00. The research results are that tourist attractions show the level of achievement of respondents with an average score of 75.1 with a good category, facilities in tourist destination areas show overall with an average score of 67.18 with a good category, but the provision of food and drink has the average value is 60.22 in the quite good category, accessibility shows overall with a value of average is 66.11 in the good category, but the condition of the parking lot and road conditions has value of average is of 63.65 and 63.31 in the category quite good, the destination image shows overall with value of average is of 72.48 in the good category, and prices for tourists show overall with an average value of 70.74 in the good category.